Control de la infección anquilostomiásica por tratamiento quimioterapeútico masivo en Costa Rica - Swartzwelder, J. C. (1972)
Tetrachloroethylene administrared to a population og 600 persons on a coffee plantation, San José, Costa Rica, in four doses six weeks apart, and subsequently in yearly doses during the following four, reduced the pre-valence of hookworn from 56% to 8%.